(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
Background: Salmonella thyphi and Salmonella paratyphi A are the members of Enterobactoriaceae and gram negative rods causing typhoid fever & partyphoid fever respectively. Automated blood culture system is the standard diagnostic method. Objective: The purpose of the present study was to see the prevalence and antibiotic resistance pattern of Salmonella typhi and Salmonella paratyphi A isolated by automated blood culture system. Methodology: This cross-sectional study was done in the Microbiology Lab at IBN Sina D. Lab and consultation center, Doyagonj, Dhaka, Bangladesh from January 2019 to June 2019. Blood culture was performed by automated blood culture method. Sensitivity pattern of antibiotic was measured by Disk diffusion method. Result: A total of 3240 blood samples were collected from suspected patients. Among them, bacteria were isolated 336 (10.37%). The most common isolated bacteria were Salmonella typhi which was 261(77.68%) cases and Salmonella paratyphi A which was in 60 (17.86%) cases. Salmonella typhi is the most common organism and showed sensitivity pattern to imipenem 97.3%, colistin 80.46% and amikain 77.4% and Salmonella paratyphi A showed. Sensitivity pattern to imipenem 93.3% and amikacin 83.3%. Conclusion: In conclusion high rate of Salmonella typhi and Salmonella paratyphi A are isolated during blood culture showing less sensitive to imipenem and amikacin. Bangladesh Journal of Infectious Diseases 2020;7(2):57-60